Strategi Manajemen Komunikasi Pimpinan dalam Meningkatkan Kualitas Pelayanan Karyawan di Brastagi Supermarket Medan - Damayanti, Astri; Hardiyanto, Sigit (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
The communication management strategy of a company's leadership is the key to a company's managerial system in improving service quality. Brastagi Supermarket is one of the companies that is considered to have quite good service, this is proven by the number of consumers who shop at Brastagi supermarket from year to year increasing or being able to maintain the number of consumers every month at 140 thousand consumers. If you don't have good service quality, consumers will move and shop at other supermarkets. Therefore, the aim of the research is to find out about leadership communication management strategies in improving the quality of employee service at Brastagi Supermarket Medan. The type of research used is qualitative, using interview data collection methods, and using data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the leadership communication management strategy in improving the quality of employee service at the Brastagi Supermarket in Medan has been carried out well by compiling and designing job descriptions for employees, providing guidance to have a friendly attitude, be polite, smile and be honest.